Investigating Particle Size‐Dependent Redox Kinetics and Charge Distribution in Disordered Rocksalt Cathodes. (2nd February 2022) - Zhang, Yuxin; Hu, Anyang; Liu, Jue; Xu, Zhengrui; Mu, Linqin; Sainio, Sami; Nordlund, Dennis; Li, Luxi; Sun, Cheng‐Jun; Xiao, Xianghui; Liu, Yijin; Lin, Feng
Abstract: Understanding how various redox activities evolve and distribute in disordered rocksalt oxides (DRX) can advance insights into manipulating materials properties for achieving stable, high‐energy batteries. Herein, the authors present how the reaction kinetics and spatial distribution of redox activities are governed by the particle size of DRX materials. The size‐dependent electrochemical performance is attributed to the distinct cationic and anionic reaction kinetics at different sizes, which can be tailored to achieve optimal capacity and stability. Overall, the local charged domains in DRX particles display random heterogeneity caused by the isotropic delithiation pathways. Owing to the kinetic limitation, the micron‐sized particles exhibit a holistic "core‐shell" charge distribution, whereas sub‐micron particles show more uniform redox reactions throughout the particles and ensembles. Sub‐micron DRX particles exhibit increasing anionic redox activities yet inferior cycling stability. In summary, engineering particle size can effectively modulate how cationic and anionic redox activities evolve and distribute in DRX materials. Abstract : Controllable Li‐ion kinetics and depth‐dependent cationic/anionic redox reactions reveal the origin of size‐dependent electrochemical performance in disordered‐rocksalt materials. The work sheds light on the particle engineering for balancing the energy density and cycle life of disordered‐rocksalt cathodes.